Analysis of the Constitutional Court’s the Judge's Decision Ratio in Interpreting the Meaning of Riots (in Constitutional Court Decision No. 115/PUU-XXII/2024) - Ahmad Saifuddin (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines Constitutional Court Decision Number 115/PUU-XXII/2024 regarding the interpretation of the term "riot" (kerusuhan) in Article 28 paragraph (3) and Article 45A paragraph (3) of the ITE Law. Previously, the ambiguity of this phrase often led to the criminalization of public criticism on digital platforms. The researcher employs a normative-juridical method, utilizing statutory and case-based approaches to analyze the Constitutional Court judges' "ratio decidendi". The findings indicate that the Court now restricts the meaning of "riot" strictly to public disturbances in the physical realm, rather than mere heated exchanges of opinion in cyberspace. The Court based its ruling on the principle of legality (lex certa) and the protection of freedom of expression in accordance with ICCPR standards. This decision effectively prevents the over-criminalization of public opinion. The study contributes an analytical framework for law enforcement officials and legislators to address the vague, "elastic" clauses of the ITE Law. Furthermore, it expands the academic discourse regarding the boundaries of criminal law interpretation within Indonesia's cyberspace.